Building Teacher Capacity in English Language Teaching in Vietnam: Research, Policy and Practice, 1st edition - Le, Van Canh (Routledge, 2020)
This timely volume opens a window on issues related to English language education in Vietnam. The authors consider that teacher quality is the key factor to be considered if the national English language curriculum outcomes are to be achievable. Aiming to shed light on key issues recently observed in the Vietnamese landscape of English language education, it examines the complexity of the institutionalization of the standardized English proficiency policy, which has been in force since 2008. That policy uses the Common European Framework of References for Languages (CEFR) as the model to set the standards and levels of proficiency for teachers, learners and state employees.